Evaluation of Existing Bond-Slip Relations for CFRP-Steel Joints and New Model for Linear and Nonlinear Adhesives - Mohammed J. Altaee; Sarmed A. S. Altayee; Majid M. A. Kadhim; Akram Jawdhari; Ali Majdi; Ali Chabuk; Nadhir Al-Ansari (Advances in Civil Engineering)
Existing bond-slip (τ-s) relations for fibre-reinforced polymer (FRP)-steel joints employ different shapes and mathematical expressions, inferring that their predictions of failure load and mode, and other interface properties, might be inconsistent or inaccurate. In this study, predictions of four widely used τ-s relations are evaluated using a large experimental database of 78 double-lap FRP-steel specimens. To facilitate the evaluation process, a robust finite element (FE) model is developed for each test, implementing data from either of the existing τ-s relations to define the FRP-steel interface. Comparisons between test and FE results indicated that the existing τ-s models were unable of predicting the ultimate load (Pu) and effective bond length (Leff) of FRP-steel joints, or the relation between Pu and bond length and that between Leff and FRP modulus (Ef). A new τ-s model is developed based on an inverse FE simulation, comparison with experimental results, and regression analysis. It considers the effects of Ef, the type of FRP reinforcement (sheet or plate), and applies to both linear and nonlinear adhesives. The model predictions were validated by comparing with results from small bond tests and large FRP-strengthened steel beams tested under bending, yielding excellent results for Pu, failure mode, and all other interfacial properties.